Finnish and Japanese Nursing Students' Attitudes Toward Older Adults: A Comparative Study - Eloranta, Sini; Rauhala, Auvo; Mört, Susanna; Kato, Yasuko; Konno, Rie (Wiley, 2026)
Introduction
Understanding nursing students' attitudes toward older adults is important as these attitudes influence their career choices and the quality of future gerontological care for older adults.
Methods
The aim of this study was to explore and compare attitudes toward older adults among nursing students in Finland and Japan. A cross-sectional comparative design was employed. Data were collected in 2024 using a structured questionnaire, which included demographic variables and Kogan's Attitude toward Old People Scale (KAOP). The participants consisted of 65 nursing students from Finland and 74 nursing students from Japan. Data were analysed using descriptive and comparative methods, and regression analysis to examine associations between KAOP scores and background factors.
Results
Japanese nursing students had more positive attitudes and greater score variability (KAOP mean 127.0, SD 10.9) than Finnish nursing students (KAOP mean 115.9, SD 5.9). The mean difference of 11.1 (95% CI: 8.2–14.0) was statistically highly significant p < 0.001, with a large Cohen's d effect size (1.27).
Conclusion
The observed differences may be influenced by the cultural and structural contexts of aged care in Finland and Japan.